Modeling of the induced plastic anisotropy fully coupled with ductile damage under finite strains. (1st March 2017) - Badreddine, H.; Yue, Z.M.; Saanouni, K.
Highlights: For an accurate plastic anisotropy description, non-associative plasticity framework is considered for which equivalent stresses in yield function and in plastic potential are separately defined. The induced plastic anisotropy is described by distortion of yield surface and plastic potential based on Francois (2001) approach. Full coupling with isotropic ductile damage is formulated. Abstract: The introduction of the kinematic hardening induced distortion of the yield surface is expected to enhance the capability of the model in simulating the material behavior under complex loading paths occurring during sheet metal forming processes.In this work non-associative elastoplastic anisotropic constitutive equations accounting for mixed nonlinear hardening and fully coupled with isotropic ductile damage, is improved by considering the distortion of the yield subsequent surfaces. A convenient "distortion" deviatoric stress tensor S ̲ d is used in both yield criterion and plastic potential instead of the usual classical deviatoric stress tensor S ̲ . Accordingly, the yield surface distortion is controlled by three adequate material parameters named X l 1 c, X l 1 p and X l 2 c . A parametric study is conducted under simple loading paths (tension and torsion) in order to explore the capabilities of the model in describing the yield surface distorsion. Comparisons with experimental results on aluminum alloy, taken from the literature, are also given. Moreover, the influence of the subsequent yield surfaces distortion under complex non-proportional loading paths on the evolution of the plastic flow with hardening and the ductile damage are also discussed and highlighted.